INNOVATIVE DEVELOPMENT AS A FACTOR OF THE NATIONAL ECONOMY COMPETITIVENESS - E. Yu. Kuzmina; I. V. Soklakova; I. L. Surat (Вестник университета)
Russian enterprises are not paying enough attention to the issues of innovative development, while global trends demonstrate the increase of enterprises competitiveness through the introduction of innovations. Innovations are able qualitatively improve enterprise performance indicators in conditions of tough competition. For many domestic enterprises, in such conditions the innovation and its specific results could be a key criterion of success. Lack of investment is the most important problem holding back innovations. The experience of support and development of innovations in Canada and South Korea has been considered in the article. It has been concluded that in general the Russian Federation is experiencing a global transfer to an innovative economy, which in the future should be an undoubted advantage for the production of competitive products. The creation of radically new products and services, as well as the enhancement of existing ones, will allow Russian enterprises systematically improve their image, increase their business reputation, which will attract more investments.